2005
DOI: 10.1007/s10875-005-4091-5
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Circulating Levels of the Novel TNF Family Members APRIL and BAFF and Lymphoid Organization in Primary Sjögren’s Syndrome

Abstract: B cell activating factor (BAFF) and a proliferation-inducing ligand (APRIL) are members of the tumour necrosis factor superfamily. We have examined circulating BAFF and APRIL in relation to serological deviations and lymphoid organization in the salivary glands of the chronic, autoimmune disorder Sjögren's syndrome. Lymphoid organization in the shape of ectopic germinal centers were detected in 33 of 130 consecutive minor salivary gland biopsies and coincided with increased focus score and elevated levels of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
146
2
14

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 203 publications
(169 citation statements)
references
References 37 publications
7
146
2
14
Order By: Relevance
“…Interestingly, BAFF was found to be significantly up-regulated in pSjS monocytes on the mRNA level (data not shown). BAFF plays a role in the survival of (autoreactive) B cells and promotes CD40-independent class switch recombination, and has indeed been found to be increased both systemically and in the salivary glands of pSjS patients [35][36][37][38]. Interestingly, expression of CD40 by pDC was significantly higher in pSjS patients positive for anti-SS-B antibodies (data not shown).…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, BAFF was found to be significantly up-regulated in pSjS monocytes on the mRNA level (data not shown). BAFF plays a role in the survival of (autoreactive) B cells and promotes CD40-independent class switch recombination, and has indeed been found to be increased both systemically and in the salivary glands of pSjS patients [35][36][37][38]. Interestingly, expression of CD40 by pDC was significantly higher in pSjS patients positive for anti-SS-B antibodies (data not shown).…”
Section: Discussionmentioning
confidence: 86%
“…Human TSLPsecreting tonsillar epithelial cells produce BAFF to induce class switching by stimulating B cells (48). In addition, a recent human study suggested an association between circulating levels of BAFF in ectopic germinal centers of the salivary gland in primary Sjögren's syndrome (16,37). Taken together, these results suggest that TSLP, together with BAFF, produced by H. pylori-infected gastric mucosa leads to inflammatory Th2 responses and maintenance of B-cell activation.…”
Section: Discussionmentioning
confidence: 87%
“…In the investigation of both serum BAFF and APRIL, in a comparison with six healthy donors the serum levels of both BAFF and APRIL in 29 SjS patients were elevated, but compared with SjS patients without anti-SSA antibody, only the serum APRIL levels in the SjS patients with anti-SSA antibody were elevated [88].…”
Section: Sjögren's Syndromementioning
confidence: 97%